How do you simplify (x+2)+(x-2)(2x+1)?

kaliitcri 2022-02-06 Answered
How do you simplify (x+2)+(x-2)(2x+1)?
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

Deacon Osborn
Answered 2022-02-07 Author has 18 answers
To solve:
(x+2)+(x-2)(2x+1),
first multiply the two binomials on the right.
We can use the FOIL method here:
Mulitply the first terms:
x2x=2x2
Multiply the outer terms:
x*1=x
Multiply the inner terms:
-2*2x=-4x
Multiply the last terms:
-2*1=-2
Then add them:
2x2+x4x2
=2x23x2
This means that
(x2)(2x+1)=2x23x2
Now we can use this to simplify the original problem:
(x+2)+(x-2)(2x+1)
=x+2+2x23x2
=2x22x
Not exactly what you’re looking for?
Ask My Question
Biscatta9rz
Answered 2022-02-08 Author has 14 answers
Explanation:
(x-2)(2x+1)
=x(2x+1)-2(2x+1)
=2x2+x4x2
=2x23x2
So
(x+2)+(x-2)(2x+1)
=x+2+2x23x2
=2x22x
Answer:
2x22x
or
2x(x-1)
Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more